Encyclopedia of human development - Salkind, Neil J. (Gale virtual reference library, 2006)
The first comprehensive, authoritative, and informative reference work that presents state-of-the-art research and ready-to-use facts from the fields of psychology, individual and family studies, and education in a way that is not too technical. With over 600 entries organized from A-Z, this three-volume Encyclopedia covers topics as diverse as adolescence, cognitive development, education, family, gender differences, identity, longitudinal research, and much more.